Mechanical behaviour of circular steel-reinforced concrete-filled steel tubular members under pure bending loads. (June 2020) - Shi, Yan-Li; Xian, Wei; Wang, Wen-Da; Li, Hua-Wei
Abstract: To study the mechanical performance of circular steel-reinforced concrete-filled steel tubular (SRCFST) members under pure bending loads, a total of six specimens with various parameters, i.e., cross-section types of profiled steel (I or cruciform section), the loading directions (along strong or weak axis) for I section profiled steel and shear-span ratios ( m  = 2.42 or 1.82) were tested. Failure modes, lateral deflection, longitudinal strain distribution, bending moment-curvature ( M - ϕ ) curves and flexural capacity were analysed, respectively. In addition, the numerical models of SRCFST members were established in ABAQUS to analyse the flexural behaviour. Moreover, a simplified calculation formula was also proposed to predict the flexural capacity. The results show that specimens exhibit a flexural failure mode instead of local buckling. Deflection curves of the specimens are similar to the sinusoid shape. The loading directions and cross-section types of profiled steel would affect the flexural capacity of SRCFST members owing to the changing of the moment of inertia. The FEA model was verified by the experimental results and good agreements were achieved in terms of the failure mode and M - ϕ curves. The steel tube carries most of the bending moment by analysing the M - ϕ curves of each component. In addition, the test results are compatible with the proposed formulas, and therefore the calculation method could be used in engineering design.